2018
DOI: 10.12688/f1000research.13396.1
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a yeast malate dehydrogenase 2 (Mdh2) antibody tested for use in western blots

Abstract: Malate dehydrogenases (Mdhs) reversibly convert malate to oxaloacetate and serve as important enzymes in several metabolic pathways. In the yeast Saccharomyces cerevisiae there are three Mdh isozymes, localized to different compartments in the cell. In order to identify specifically the Mdh2 isozyme, GenScript USA produced three different antibodies that we further tested by western blot. All three antibodies recognized the S. cerevisiae Mdh2 with different background and specificity properties. One of the ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…To ensure that the peroxisomal localization of Mdh2 and its dependence on Mdh3 and Pex5 is not a result of the GFP tagging, we generated a specific antibody that recognizes Mdh2 but not the other Mdh isoforms (Gabay-Maskit et al, 2018). Analysis of subcellular fractions clearly demonstrated that native and un-tagged Mdh2 also co-sediments with peroxisomes (Figure 3E,control) and that its peroxisomal localization is dependent on the presence of Mdh3 ( Figure 3E, mdh3).…”
Section: The Peroxisomal Localization Of Mdh2 Is Pex5-and Mdh3-dependentmentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure that the peroxisomal localization of Mdh2 and its dependence on Mdh3 and Pex5 is not a result of the GFP tagging, we generated a specific antibody that recognizes Mdh2 but not the other Mdh isoforms (Gabay-Maskit et al, 2018). Analysis of subcellular fractions clearly demonstrated that native and un-tagged Mdh2 also co-sediments with peroxisomes (Figure 3E,control) and that its peroxisomal localization is dependent on the presence of Mdh3 ( Figure 3E, mdh3).…”
Section: The Peroxisomal Localization Of Mdh2 Is Pex5-and Mdh3-dependentmentioning
confidence: 99%
“…The Mdh2 antibody was produced by GeneScript, USA, using a specific Mdh2 peptide as an immunogen: MPHSVTPSIEQDSLC, and was verified by us for specificity and activity (dil. 1:2.500) (Gabay-Maskit et al, 2018…”
Section: Antibodiesmentioning
confidence: 99%
“…60 And MDH2 can be identified by specific antibodies with higher and higher specificity. 61 As research showed, cytosolic and mitochondrial MDH activities and cytosolic ratio of MDH/LDH activity in leukocytes from the whole blood of race horses were significantly higher than those of riding horses. It was considered to reflect the elevation of energy metabolism in animal tissues.…”
Section: Is It Feasible To Detect Mdh In Clinic?mentioning
confidence: 93%
“…3C). Among them, MDH2 plays a role in cell metabolism and amino acid acetylation [16]. GOT2 is necessary for metabolite exchange between mitochondria and cytoplasm and plays a crucial role in amino acid metabolism [17].…”
Section: Prediction and Analysis Of Interacting Protein With Espfmentioning
confidence: 99%